STEMinism. - Myers, Kristen; Gallaher, Courtney; McCarragher, Shannon (Journal of Gender Studies, 2019)
Science, Technology, Engineering, and Mathematics (STEM) fields play important roles in creating knowledge for society and pathways to power, resources, and authority for scientists, yet women, and people of color, have historically been underrepresented in STEM fields. Various approaches have attempted to diversify the pipeline into these fields. Drawing on semi-structured interviews with 45 undergraduate students from a large Midwestern university in the US, we find that students have benefitted from programs aimed at recruiting women, and people of color, into STEM. Feminist approaches to raise awareness about gender gaps in STEM have enabled students to recognize gender differences, but they have not gone far enough yet. Rather than understanding and problematizing gendered power dynamics in the classroom, lab, and workplace, students espouse what we call 'STEMinism': an individualistic lens that, in many ways, asks women in STEM to recognize the problem and fix it for themselves. Improving the representation of women, and people of color, in STEM requires a concentrated critique and interruption of the structural forces that perpetuate sex-segregation in STEM. We offer suggestions for increasing the effectiveness of programs designed to end gender inequality in STEM fields.